Photocatalytic Activity under Simulated Sunlight of Bi-Modified TiO2 Thin Films Obtained by Sol Gel - D. A. Solís-Casados; L. Escobar-Alarcón; V. Alvarado-Pérez; E. Haro-Poniatowski (International Journal of Photoenergy)
The synthesis of Bi-modified TiO2 thin films, with different Bi contents, is reported. The obtained materials were characterized by energy-dispersive X-ray spectroscopy (EDS), X-ray photoelectron spectroscopy (XPS), Raman spectroscopy (RS), X-ray diffraction (XRD), photoluminescence (PL), and diffuse reflectance spectroscopy (DRS), in order to obtain information on their chemical composition, vibrational features, and optical properties, respectively. Compositional characterization reveals that the bismuth content can be varied in an easy way from 0.5 to 25.4 at. %. Raman results show that the starting material corresponds to the anatase phase of crystalline TiO2, and Bi addition promotes the formation of bismuth titanates, Bi2Ti2O7 at Bi contents of 10.4 at. % and the Bi4Ti3O12 at Bi contents of 21.5 and 25.4 at. %. Optical measurements reveal that the band gap narrows from 3.3 eV to values as low as 2.7 eV. The photocatalytic activity was tested in the degradation reaction of the Malachite Green carbinol base dye (MG) as a model molecule under simulated sunlight, where the most relevant result is that photocatalytic formulations containing bismuth showed higher catalytic activity than pure TiO2. The higher photocatalytic activity of MG degradation of 67% reached by the photocatalytic formulation of 21.5 at. % of bismuth is attributed to the presence of the crystalline phase perovskite-type bismuth titanate, Bi4Ti3O12.